Allele-specific electrical genotyping for diagnosis of transthyretin amyloidosis - Muhammad Tayyab; Neeru Gandotra; Jianye Sui; Curt Scharfe; Mehdi Javanmard (Communications Engineering)
Abstract Clinical genetic testing often takes days to weeks, but rapid, affordable tests during outpatient visits could significantly benefit patients. This is crucial for detecting common, actionable point mutations, such as those linked to hereditary transthyretin (TTR) amyloidosis, which is often underdiagnosed in individuals of West African ancestry with congestive heart failure. Here we developed a method for detecting known DNA variants using allele-specific polymerase chain reaction (ASPCR) and electrical impedance. Oligonucleotide primers were designed to selectively amplify the ancestral and variant allele of TTR c.424G>A (p.Val142Ile). PCR products were detected in solution using passive-flow microfluidic impedance cytometry across multiple excitation frequencies. Impedance responses correlated with DNA concentration, allowing for the calculation of a robust DNA quantification score. TTR V142I genotypes from six patients (four heterozygous, two wildtype) matched results from gel electrophoresis and sequencing. Future improvements will focus on reducing DNA input requirements and enabling multiplex variant detection.